A indústria de confecção no Brasil: trabalho, produtividade e produção em rede - o caso da iniciativa do setor confeccionista nas cidades de Cerquilho e Tietê - Balian, Jose Eduardo Amato (2017)
This doctoral thesis had as its proposal the analysis of local Productive Arrangements of the confectionery sector in the cities of Cerquilho and Tietê and its socioeconomic impacts, reflections on work relations and strategic objectives. The proposal is based on the changes of the economy, the processes of production management, the relations between capital and labor and the human relationship regarding family, professional and personal interactions. The thesis had as general objective of reflection the verification of the impact of the Brazilian crisis in the APL of Cerquilho and Tietê and its consequences in the social areas and sought to identify the externalities that directly or indirectly affected the APL. In order to meet the established objectives, the case study methodology was used, with comparative and documentary analysis, considering a survey of the data. Contributed to the decision making: monitoring research developed by Sebrae SP; Globalized enterprise management models; analysis of comprehensive and specific indicators and interviews. It can be inferred up to the present time, and in accordance with the field and documentary research currently available in the areas addressed that the hypothesis was proven, insofar as the consequences for the organizations belonging to the APL were not different from the organizations outside the APL, that is, closing, unemployment and falling GDP, with all relevant social implications. The research sought to show that the benefits generated by APL extrapolate the improvements observed within the group and gains also appear in social areas. If there is a frustration with the group, it is that the people realized that the gain could be much greater, minimizing the effects of the Brazilian crisis